Factors Influencing Accountant Intention to Use Illegal Software - Astarani, Juanda (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2012)
Purpose This research studies the factors influencing accountant intention to use illegal software. This research aim also want to know whether accountant that learning about recognizing, record-keeping and measurement of intangible assets will have more strong perception about intangible assets equal to tangible assets and tend to disagree to the action of using illegal software compared to other profession.. Methodology This headline news use 87 samples of accountant, and 59 samples of Information Technology postgraduate student. In analyze data to test the hypothesis this research use the Structural Equation Modeling by using Partial Least Square Software. Researcher choose accountant because accountant learning about recognizing, record-keeping and measurement of intangible assets. The other profession in this research is deputized by information technology postgraduate student from one of University in Indonesia. Findings: The factors influencing accountant intention to use illegal software are attitude toward using illegal software and perceived behavioral control (PBC). This research also indicate that the perception of punishment severity, perceived usefulness, and perception of intangible assets equal to tangible assets have significant effect to attitude toward using illegal software, punishment certainty have significant effect to perceived behavioral control (PBC). This research also find if accountant tend to have more strong perception about intangible assets equal to tangible assets and tend to disagree to the action of using illegal software compared to other profession.. Research limitations/implications This research limitation is the small amount of sample and only from one city in Indonesia. Practical implications Even this research use small amount of sample, this research give the explanation about factors that influence someone intention to use illegal software, and show if the education of intangible asset will affect that intention. Social implications This research can give idea for government and other authorities about how to give understanding for the people to do not use illegal software. Originality/Value This research gives new point of view of study in software piracy problem. Software is intangible asset, but if someone steals it the owners still have the software, this research give new idea to maximize the understanding of intangible asset because it can reduce the intention to use illegal software. Key Words: Software Piracy, Intangible assets, Perceived behavioral control, Attitude, Intention.